Pengaruh Kepuasan Kerja dan Beban Kerja Terhadap Turnover Intention pada Perawat Rumah Sakit Arafah Anwar Medika Sukodono Sidoarjo - Ajeng Arum Isfania; Endang Iryanti (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
In today's era of globalization, companies or organizations must compete and adapt to address threats and competitors in order to remain contemporary. Human resources (HR) become a key factor that plays a role in achieving the company's goals in its commercial endeavors. HR issues are often related to turnover intention faced by companies/organizations. This study aims to identify the impact of job satisfaction and workload on turnover intention among nurses at Arafah Anwar Medika Hospital Sukodono, Sidoarjo. The research sample consists of 48 nurses at Arafah Anwar Medika Hospital Sukodono. Data were collected through the distribution of questionnaires to the nurses and analyzed using the Partial Least Square (PLS) approach, involving reliability tests, validity tests, and hypothesis testing. The findings of the study show that job satisfaction has a negative and significant effect on turnover intention, while workload has a positive and significant effect on turnover intention.